Evaluation of liquid xylanase and phytase added after broiler feed pelletization - Géssica Paula Tobias; Leonardo Miguel Fabiani; Heloísa Pagnussatt; Alicia Dal Santo; Marcos de Lima; Felipe Leite; Caroline Schmidt Facchi; Gustavo Zaccaron; Gabriel Hoinoski; Edemar Aniecevski; Maurício Vicente Alves; Gabriela Miotto Galli; et al. (Revista Brasileira de Zootecnia, 2023)
ABSTRACT The objective of this study was to evaluate whether the addition of the enzymes phytase and xylanase, isolated or associated, in the liquid form after feed pelletization could improve energy utilization and digestibility of calcium and phosphorus by broiler chickens. Three experiments were performed using 120 birds each, divided into five treatments with eight replicates per group (n = 3), identified as: experiment 1 (xylanase: control, 1000 IU, 1500 IU, 2000 IU, 2500 IU), experiment 2 (phytase: control, 500 FTU, 1000 FTU, 1500 FTU, 2000 FTU), experiment 3 (xylanase + phytase: control, 3000 IU + 500 FTU, 3000 IU + 1000 FTU, 3000 IU + 1500 FTU, 3000 IU + 2000 FTU). Samples for digestibility tests were collected at 14 to 21 days of age. Therefore, the inclusion of liquid phytase and liquid phytase + xylanase after pelletization in broiler diets has become a relevant way to reduce the inclusion of inorganic P, which can reduce the cost of feed and P excretion in the environment. Furthermore, it is an interesting strategy to avoid enzyme denaturation in the pelleting process.